Estimation of dielectric constant for various standard materials using microstrip ring resonator - Low, Pek Jin; Esa, Fahmiruddin; You, Kok Yeow; Abbas, Zulkifly (UTHM Publisher, 2017)
Microstrip ring resonator (MRR) is known for dielectric constant determination and many studies used Teflon as a standard sample. However, there are many other materials available which able to perform better or equivalence as the Teflon in calibrating certain dielectric constant measurement. This paper presents simulation of the MRR to investigate frequency shift of materials for dielectric constant estimation using the CST STUDIO SUITE 2016 software. The MRR was designed on RT/Duroid®5880 substrate (εr = 2.2, tanδ = 0.0004) with 50 Ω matching impedance where microstrip width, substrate thickness and ring mean radius were 4.893, 1.575 and 14 mm, respectively to resonate at 2.65340 GHz. Teflon, Polyimide, Isola FR408, Arlon AD250, Arlon AD270 and Gil GML1032 were alternately selected to be placed on top of the MRR as a standard sample to obtain the frequency shift. The frequency shifts for the above materials were 2.56932, 2.46149, 2.44680, 2.53748, 2.52007 and 2.48608 GHz, correspondingly. The differences in frequency shift were used in NetBeans IDE 8.1 algorithm of Java for dielectric constant calculation. The results indicated that Polyimide and Arlon AD250 had the lowest and highest mean percentage error of 0.83536 and 1.76505 %, respectively. Hence, Polyimide might as well be the most suitable candidate as a standard sample in MRR technique for dielectric constant measurement.